Estudio de polimorfismos genéticos en CYP3A4 y CYP2D6, y su papel en la susceptibilidad a cáncer de mama - Fleitas B., Laura; Durán M., Noelia; Miranda M., Carla; Lee C., Kuen; Quiñones S., Luis (Revista Hospital Clínico Universidad de Chile, 2013)
Background: Breast cancer is the first cause of death in women in Chile and worldwide. One of the causing factors is the exposition to endogenous and exogenous estrogens which stimulate cell proliferation. Estrogens are metabolized by cytochrome P450 enzymes, mainly CYP3A4 and CYP2D6, which participate in estradiol hydroxylation to 2-hydroxyestradiol and/ or 4-hydroxyestradiol, facilitating their excretion from the body. Thus, polymorphisms in these enzymes alter the plasma estrogen concentration and its excretion rate. Moreover, CYP3A4*1B polymorphism have been associated to breast cancer risk and also with early menarche. Goal: To establish potential associations between breast cancer risk and CYP3A4*1B and CYP2D6*4 genetic variants in patients compared with healthy volunteers. Methods: The Research was authorized by the Ethical Comitee of Military Hospital of Santiago, Chile. Patients signed an informed consent and genomic DNA was obtained for genotyping of CYP3A4 and CYP2D6 through PCR-RFLP. Results: Obtained genotype frequencies in patients for CYP3A4*1B were: 0.821 for CYP3A4*1/*1; 0.184 for CYP3A4*1/*1B; 0.789 for CYP2D6*1/*1 and 0.211 for CYP2D6*1/*4. No recessive homozygote mutant genotypes were detected in patients (CYP3A4*1B/*1B or CYP2D6*4/*4). enotype frequencies for healthy volunteers were 0.890 for CYP3A4*1/*1; 0.110 for CYP3A4*1/*1B; 0.735 for CYP2D6*1/*1; 0.245 for CYP2D6*1/*4 and 0.019 for CYP2D6*4/*4. It was observed a higher frequency of CYP3A4*1/*1B in patients in relation to healthy volunteers, however the difference was not statistically significant. Conclusions: This research is a first approach to the study of breast cancer susceptibility associated to CYP3A4 and CYP2D6 variants in Chilean patients. Even though we do not find an statistically significant association, the potential relationship observed for CYP3A4*1B (OR=1,83, IC=0,63-5,22, p= 0,212) should be confirmed in a bigger study, so that these findings could be extrapolated to clinical therapeutics in breast cancer patients in order to favor early detection of the risk to acquire the pathology.